Temperature variations in a parked vehicle - Dadour, I.; Almanjahie, I.; Fowkes, N.; Keady, Grant; Vijayan, K. (Elsevier, 2011)
There were two reasons why this work was conducted. The first was to help determine the time of death of suicide and homicide victims inside vehicles. The second was to investigate the serious threat to life of children or pets left in stationary vehicles on a hot summers day. This paper demonstrates that when a vehicle is parked in the sun, temperature levels in the cabin of the vehicle can be more than 20 °C above the ambient temperature. A simple ‘greenhouse’ model for predicting the daily internal vehicle temperatures, using readily available local meteorological data, was developed. This statistical model was calibrated using meteorological data and temperature data collected on parked vehicles over several summer seasons. The model uses environmental temperature and radiation data as input, and is shown to predict cabin temperatures to within about 1 °C. Both the data collected and the model developed show that the temperature inside the cabin of a black vehicle is typically 5 °C higher than that inside a white vehicle on a hot summer day. Also lowering the driver's window of the vehicle by 2.5 cm typically reduces cabin temperatures by about 3 °C, which is not sufficient to reduce significantly the safety concerns for children or pets left in parked vehicles.